A study on the natural host range of Enterocytozoon hepatopenaei in different species of shrimp and co-habiting aquatic fauna - Shirsak Mondal; Deepika, A.; Hundare, Sagar; Poojary, Nalini; Abraham, T. J; K. Sreedharan; Tripathi, Gayatri; K. V. Rajendran (Indian Journal of Fisheries, 2023)
Enterocytozoon hepatopenaei (EHP) is a serious pathogen impacting farmed shrimp production in Asian countries. Though many aquatic organisms were reported to be susceptible to EHP, the full range of susceptible hosts, which have the potential to transmit the pathogen to shrimp has not been identified. In this study, a range of farmed and wild invertebrates and other cohabiting fauna from different ecological niches located in the coastal and inland saline areas were subjected to PCR-based detection employing primers targeting three different genes coding for small subunit (ssu) rRNA, spore wall protein (SWP) and β-tubulin. The PCR analysis with ssu-rRNA primers showed positive amplification in Penaeus vannamei, Penaeus monodon, Penaeus indicus, marine shrimps, aquatic insect, mud crabs, freshwater crab and violet clam. PCR using SWP primers detected EHP in P. vannamei, P. monodon, aquatic insect and marine crabs, while the β-tubulin primers resulted in positive amplification only in mud crabs and P. vannamei. The PCR amplicons revealed 99-100% identity with the sequences of EHP. The present study forms the first attempt to screen a wide range of aquatic fauna for EHP employing three different PCR tests and the findings are significant as these organisms have the potential to be carriers of EHP and are likely to transmit the parasite to shrimp culture systems. Keywords: Co-habiting aquafauna, Enterocytozoon hepatopenaei, EHP, Host range, Shrimp culture